Preparation method of copper-based alloy quantum dot / metal oxide composite catalyst and application of copper-based alloy quantum dot / metal oxide composite catalyst in photocatalytic carbon dioxide reduction

By photoinduced deposition of copper-based alloy quantum dots on metal oxide substrates, an efficient photocatalyst was prepared, which solved the shortcomings of existing photocatalysts in light absorption, carrier separation and product selectivity, and achieved the effect of highly selective methane production.

CN120079387APending Publication Date: 2025-06-03NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510181629.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing photocatalysts have shortcomings in light absorption performance, carrier separation efficiency and product selectivity, especially in the generation efficiency of high value-added product methane.

Method used

Copper-based alloy quantum dot/metal oxide composite catalyst is prepared by light-induced deposition of different molar ratios of copper nitrate and other metal nitrates onto the metal oxide substrate, uniform anchoring and interface coupling of alloy quantum dots is achieved.

Benefits of technology

The catalyst exhibits high efficiency light absorption, good carrier separation and excellent product selectivity, especially in the high selective production of methane and has good cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120079387A_ABST
    Figure CN120079387A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a copper-based alloy quantum dot / metal oxide composite catalyst and application of the copper-based alloy quantum dot / metal oxide composite catalyst to photocatalytic CO2 reduction, and belongs to the technical field of catalysts, and the catalyst is prepared by depositing copper nitrate and other metal nitrate in different molar ratios on a metal oxide substrate through light induction. The Cu-M alloy has a nano-sized quantum dot structure, and the composite catalyst shows excellent photocatalytic carbon dioxide (CO2) reduction performance and especially has high selectivity to methane (CH4). The catalyst provided by the invention is simple and convenient in preparation process, low in cost and environment-friendly, and has efficient catalytic activity and good cycle stability. The method is expected to have a wide application prospect in the fields of photocatalytic CO2 reduction, methane production and the like, and has an important promotion effect on clean energy development and environmental governance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and particularly relates to a preparation method of a copper-based alloy quantum dot / metal oxide composite catalyst and its application in photocatalytic carbon dioxide (CO 2 ) reduction, especially suitable for the highly selective production of methane (CH 4 ). Background Art

[0002] With the exacerbation of global climate change and energy shortage problems, the conversion of carbon dioxide (CO 2 ) into useful hydrocarbons, especially through solar-driven photocatalytic CO 2 reduction technology, has become a potential solution to environmental and energy challenges. This technology can not only reduce the concentration of CO 2 in the atmosphere, but also realize the storage and utilization of energy. However, the existing photocatalysts have significant deficiencies in many aspects, which limit their popularization in practical applications.

[0003] Firstly, the light absorption performance of the catalyst is often insufficient, and it cannot effectively utilize most of the radiation in the solar spectrum, affecting the overall efficiency of the reaction. Secondly, the generation and separation efficiency of photo-generated carriers on the catalyst surface is low, and they are prone to recombination, resulting in energy loss and thus reducing the catalytic activity. More critically, the product selectivity in the photocatalytic CO 2 reduction reaction is poor, especially there are still great challenges in the production efficiency of high-value-added products (such as methane). Currently, most catalysts are difficult to achieve good selectivity among multiple reaction paths, resulting in a complex and uncontrollable product distribution. Therefore, developing photocatalysts with high-efficiency light absorption, good carrier separation, and excellent product selectivity, especially catalysts for high-value-added products such as methane, has become the core task in the current research in this field. Summary of the Invention

[0004] The object of the present invention is to provide a copper-based alloy quantum dot / metal oxide composite catalyst for highly efficient photocatalytic reduction of carbon dioxide (CO 2 ). This catalyst is prepared by photoinduced deposition of copper nitrate with different molar ratios and other metal nitrates on a metal oxide substrate, and has excellent catalytic activity and cycle stability. Another object of the present invention is to provide a preparation method of this catalyst and its application in photocatalytic CO 2 reduction, especially for the highly selective production of methane (CH 4 ).

[0005] The copper-based alloy quantum dot / metal oxide composite catalyst described in the present invention is formed by photoinduced deposition of copper nitrate and other component metal nitrates with different molar ratios onto an oxide substrate. The elements that form an alloy with the copper element in copper nitrate include one of Co, Ni, In, Bi, Ln (Ln = La, Ce, Pr, Nd, Sm, Gd). Preferably, the metal oxide substrate is TiO 2 , Cu 2 O, SrTiO 3 , WO 3 . The expression of the composite catalyst is: Cu x Ln y -TiO 2 , Cu x Co y -TiO 2 , Cu x Ni y -SrTiO 3 , Cu x In y -Cu 2 O, Cu x Bi y -WO 3 (1 ≤ x, y ≤ 7); where the ratio of x and y is optimized and determined by adjusting the molar ratio of nitrates.

[0006] Preferably, the average size of the alloy is 1 - 2 nm.

[0007] Preferably, the loading mass percentage in the copper-based alloy quantum dot / metal oxide composite catalyst is 0.9 - 1.5%.

[0008] The preparation method of the copper-based alloy quantum dot / metal oxide composite catalyst described in the present invention includes the following steps: 1) Ultrasonically disperse the metal oxide in absolute ethanol; 2) After mixing copper nitrate and the required other nitrates, add absolute ethanol and ultrasonically treat; 3) Inject the nitrate solution prepared in step 2) into the solution of step 1); 4) Transfer the prepared mixed solution to a glass reactor equipped with a transparent quartz optical window at the top; 5) Seal the reactor, set a magnetic stirrer and stir, and externally connect a condensing water circulation; 6) Continuously irradiate the mixed solution with a simulated solar light source excited by a xenon lamp; 7) Separate and wash the product obtained in step 6), dry and grind to obtain the composite photocatalyst.

[0009] Preferably, in step (1), the mass of the metal oxide is 100 mg - 500 mg, and the volume of absolute ethanol is 50 - 100 mL.

[0010] Preferably, in step (2), the total molar amount of nitrates is 0.1 mmol - 0.5 mmol.

[0011] Preferably, in the step (5), the rotor stirring speed is 300 - 450 rmp, and the condensed water temperature is controlled at 15 - 25 °C.

[0012] Preferably, in the step (6), the height of the xenon light source is 10 - 20 cm above the mixed solution; the wavelength range of the xenon light is 320 - 780 nm; the light intensity is controlled at 100 - 500 mW / cm -2 ; the irradiation time is 20 - 60 min.

[0013] More preferably, in the step (6), the light irradiation time is 30 min.

[0014] Preferably, the specific steps of the step (7) are as follows: centrifuge the product after photo-deposition, with a rotation speed of 9000 rmp / min and a time of 10 min. Then add deionized water and wash three times, and finally dry in a vacuum drying oven at 60 °C for 12 h.

[0015] Use of the copper-based alloy quantum dot / metal oxide composite catalyst of the present invention in the preparation of an alloy-supported catalyst.

[0016] Use of the copper-based alloy quantum dot / metal oxide composite catalyst of the present invention in photocatalytic reduction of carbon dioxide.

[0017] Use of the copper-based alloy quantum dot / metal oxide composite catalyst of the present invention in the efficient production of methane by photocatalytic reduction of carbon dioxide.

[0018] The operation process for detecting the copper-based alloy quantum dot / metal oxide composite catalyst of the present invention is as follows:

[0019] a) Prepare a detection sample of the copper-based alloy quantum dot / metal oxide composite catalyst film. First, weigh 20 mg of the prepared composite catalyst powder, add 5 mL of deionized water, ultrasonically disperse it evenly, and then drop it into a circular quartz groove with a diameter of 45 mm. Then place the quartz groove in a vacuum oven at 60 °C and dry for 6 h for standby;

[0020] b) Before the photocatalytic test, support the quartz groove with a quartz tray and inject 2 mL of deionized water around the quartz tray; purge the reaction chamber with high-purity argon for 10 min, and then evacuate the reactor and introduce high-purity CO 2 gas until the pressure in the reaction chamber is about 90 kPa; use a plunger pump to help the gas diffuse.

[0021] c) After adsorbing for 20 min under dark conditions, place a simulated solar xenon light source on the top, and automatically and online detect the gas in the chamber every 1 h.

[0022] Preferably, a xenon light source is placed about 10 cm directly above the mixed solution; the wavelength range of the xenon light is 320 - 780 nm; the light intensity is controlled at 100 - 500 mW cm -2 .

[0023] Advantages

[0024] Compared with the prior art, the present invention has the following remarkable advantages: 1. The in-situ photodeposition method is used to construct a copper-based alloy quantum dot / metal oxide heterostructure, realizing the uniform anchoring and interfacial coupling of alloy quantum dots. This process has the characteristics of mild reaction conditions, low raw material cost, high repeatability, etc., breaking through the dependence on high-temperature reduction conditions in the preparation of traditional alloy catalysts; 2. The copper-based alloy quantum dot / metal oxide composite catalyst synthesized by the present invention has high catalytic reaction activity, stable catalytic performance, good carbon dioxide reduction effect, and high selectivity for methane; especially through precise regulation of alloy components (Cu 7 Pr 1 -TiO 2 and other preferred combinations), the CO 2 →CH 4 reaction path dominates and significantly inhibits the formation of by-product H 2 . This alloy quantum dot modification strategy has multiple advantages, which is beneficial to the efficient photocatalytic synthesis of methane: 1) Photoinduction promotes the formation of partial oxygen vacancies in the substrate oxide, which is beneficial to the adsorption of CO 2 and the dissociation of H 2 O; 2) The alloy loading effectively shifts the Fermi level to a more favorable redox potential; 3) The Cu-M bimetallic synergistic effect is beneficial to stabilizing the active zero-valent Cu (Cu 0 ), and at the same time reduces the energy barrier of the rate-determining step of *CO→*CHO; 4) The built-in electric field at the heterojunction interface between the alloy quantum dots and the substrate metal oxide accelerates the separation and migration of carriers. Description of the Drawings

[0025] Figure 1 is the transmission electron microscope (TEM) image of the Cu 7 Pr 1 -TiO 2 composite material in Example 1 of the present invention.

[0026] Figure 2 is the wide-spectrum scanning X-ray photoelectron spectroscopy (XPS) image of the Cu 7 Pr 1 -TiO 2 composite catalyst in Example 1 of the present invention.

[0027] Figure 3 is the Cu 7 Pr 1-TiO 2 High-resolution elemental peak separation spectra of the composite catalyst by XPS.

[0028] Figure 4 For the composite catalyst Cu 7 Pr 1 -TiO 2 Product distribution diagram for continuous reaction for 4 h.

[0029] Figure 5 For the composite catalyst Cu 7 Pr 1 -TiO 2 Cyclic stability test diagram within 72 h.

[0030] Figure 6 For the composite catalyst Cu 1 Co 1 -TiO 2 Product distribution diagram for continuous reaction for 4 h.

[0031] Figure 7 For the composite catalyst Cu 1 Co 1 -TiO 2 Cyclic stability test diagram for continuous test for 24 h.

[0032] Figure 8 For the composite catalyst Cu 1 Co 1 -TiO 2 Product distribution diagram for continuous reaction for 4 h.

[0033] Figure 9 For the composite catalyst Cu 3 Ni 1 -SrTiO 3 Cyclic stability test diagram for continuous test for 24 h.

[0034] Figure 10 For the composite catalyst Cu 5 In 1 -Cu 2 Product distribution diagram of O for continuous reaction for 4 h.

[0035] Figure 11 For the composite catalyst Cu 5 In 1 -Cu 2 Cyclic stability test diagram of O for continuous test for 24 h.

[0036] Figure 12For the composite catalyst Cu of Example 5 of the present invention 3 Bi 1 -WO 3 Product distribution diagram for 4 h of continuous reaction.

[0037] Figure 13 For the composite catalyst Cu of Example 5 of the present invention 3 Bi 1 -WO 3 Cyclic stability test diagram for 24 h of continuous testing.

[0038] Figure 14 For the control sample (TiO 2 , SrTiO 3 , Cu 2 O, WO 3 ) methane production rate comparison bar chart. Detailed implementation mode

[0039] To make the purpose, technical solution and effects of the present invention clearer and more definite, the following examples are listed to further illustrate the present invention in detail. It should be noted that the specific implementation described here is only used to explain the present invention and is not used to limit the present invention.

[0040] Example 1 Preparation of Cu 7 Pr 1 -TiO 2 catalyst and evaluation of photocatalytic CO 2 reduction performance

[0041] 500 mg of TiO 2 was weighed and dispersed in 70 mL of absolute ethanol, placed in beaker 1, and ultrasonic treatment was carried out to ensure uniform dispersion. Then, a copper nitrate ethanol solution and a praseodymium nitrate ethanol solution with a concentration of 1 mg / mL were prepared and ultrasonic treatment was carried out for 30 min to obtain a uniform solution. Subsequently, 23.5 mL of the copper nitrate ethanol solution and 5.1 mL of the praseodymium nitrate ethanol solution were respectively added to beaker 1. The mixed solution was transferred to a glass reactor, equipped with a magnetic stirrer and stirred. About 10 cm directly above the reactor, a xenon lamp light source simulating sunlight was used for irradiation, and the light intensity was adjusted to 200 mW·cm-2. The reactor was evacuated by a vacuum pump, and then the light source was turned on for continuous irradiation for 30 min to synthesize Cu 7 Pr 1 -TiO 2 . The synthesized composite material was washed three times with deionized water to remove residual ethanol and nitrate ions, and finally dried under vacuum for 12 h. Under ultrasonic conditions, 20 mg of the photocatalyst was mixed with 5 mL of deionized water and dispersed in a quartz groove with a diameter of 45 mm, and then placed in a vacuum oven at 60 °C for drying for 5 h to obtain a thin film catalyst.

[0042] Photocatalytic CO 2 The reaction experiment was carried out in a closed glass gas circulation system (Labsolar-6A, Beijing Perfect Light Source Technology Co., Ltd.), where 2 mL of deionized water was added, and the water and the quartz groove coated with the photocatalyst were separated by a quartz tray. Before illumination, the gas circulation system was vacuum-treated for 15 min, and then high-purity CO 2 (99.999%) was injected. The reactor filled with high-purity CO 2 was vacuum-treated again, and high-purity CO 2 was injected to make it reach 90 kPa. The temperature was adjusted to 25 °C using circulating water. The xenon lamp was placed directly above the catalyst at a distance of about 10 cm. The gas products were detected by a gas chromatograph (GC9720 Plus) equipped with a flame ionization detector (FID) and a thermal conductivity detector (TCD). The generated gas was calibrated with a standard mixed gas, and its characteristics were determined by retention time and integration area.

[0043] Figure 1 a shows the transmission electron microscope (TEM) image of Cu 7 Pr 1 -TiO 2 . The black dot area shows the distribution of Cu 7 Pr 1 quantum dots on the TiO 2 substrate, and the average size of the quantum dots is about 1 - 2 nm. Figure 1 c is the high-resolution transmission electron microscope (HRTEM) image of the corresponding area. The lattice fringe spacings of 0.351 nm and 0.216 nm respectively belong to the (101) crystal plane of TiO 2 and the (111) crystal plane of Cu 7 Pr 1 alloy. Figure 2 and Figure 3 show the wide-scan X-ray photoelectron spectroscopy (XPS) spectrum and the peak-fitting spectra of each element of Cu 7 Pr 1 -TiO 2 . Among them, Cu, Pr, Ti, and O elements are detected and there are no extra satellite peaks in Cu 2p and Pr 3d. The above results fully indicate that Cu 7 Pr 1 alloy quantum dots are successfully prepared and uniformly loaded on the surface of TiO 2 . Figure 4 shows Cu 7 Pr 1 -TiO 2The product performance of the catalyst under continuous light irradiation for 4 h, where the methane production reached 3201.5 μmol g -1 , and the electron selectivity was as high as 96.3%. Under the conditions without a sacrificial agent and a cocatalyst, the excellent performance of this catalyst exceeded that of most photocatalysts in the current literature, showing its significant commercial application potential. Figure 5 Shows Cu 7 Pr 1 -TiO 2 The methane production of the catalyst in three consecutive cycles. The results show that there is almost no attenuation within 72 h, further demonstrating its excellent catalytic stability.

[0044] Example 2 Preparation and photocatalytic CO 1 Co 1 -TiO 2 catalyst and evaluation of its photocatalytic CO 2 reduction performance

[0045] 500 mg TiO 2 was weighed and dispersed in 70 mL of absolute ethanol in beaker 1 and sonicated to ensure uniform dispersion. Then, copper nitrate ethanol solution and cobalt nitrate ethanol solution with a concentration of 1 mg / mL were prepared and sonicated for 30 min to obtain a uniform solution. Subsequently, 12.1 mL of copper nitrate ethanol solution and 14.5 mL of cobalt nitrate ethanol solution were added to beaker 1 respectively. The mixed solution was transferred to a glass reactor equipped with a magnetic stirrer and stirred. About 10 cm directly above the reactor, a xenon lamp source simulating sunlight was used for irradiation, and the light intensity was adjusted to 200 mW·cm-2. The reactor was evacuated by a vacuum pump, and then the light source was turned on for continuous irradiation for 30 min to synthesize Cu 1 Co 1 -TiO 2 . The synthesized composite material was washed three times with deionized water to remove residual ethanol and nitrate ions, and finally dried under vacuum for 5 h. Under ultrasonic conditions, 20 mg of the photocatalyst was mixed with 5 mL of deionized water and dispersed in a quartz groove with a diameter of 45 mm, and then placed in a vacuum oven at 60 °C for drying for 5 h to obtain a thin film catalyst.

[0046] Cu 1 Co 1 -TiO 2 catalyst photocatalytic CO 2 reduction performance evaluation was the same as in Example 1. Figure 6 Shown is Cu 1 Co 1 -TiO 2Product performance graph of the catalyst under continuous light irradiation for 4 h, with the methane production of the main product reaching 275.2 μmol g -1 , and the electron selectivity reaching 88.2%. Figure 7 Shown is Cu 1 Co 1 -TiO 2 The methane production of the catalyst hardly decreased within 4 consecutive cycles, indicating good catalytic stability. It has obvious advantages over other photocatalytic material systems under the same conditions and has excellent commercial value.

[0047] Example 3 Cu 3 Ni 1 -SrTiO 3 Preparation of the catalyst and evaluation of the photocatalytic CO 2 reduction performance

[0048] 500 mg SrTiO 3 was weighed and dispersed in 70 mL of absolute ethanol, placed in beaker 1, and ultrasonic treatment was carried out to ensure uniform dispersion. Then, copper nitrate ethanol solution and nickel nitrate ethanol solution with a concentration of 1 mg / mL were prepared and ultrasonic treated for 30 min to obtain a uniform solution. Subsequently, 21.8 mL of copper nitrate ethanol solution and 7.2 mL of nickel nitrate ethanol solution were respectively added to beaker 1. The mixed solution was transferred to a glass reactor equipped with a magnetic stirrer and stirred. About 10 cm directly above the reactor, a xenon lamp source simulating sunlight was used for irradiation, and the light intensity was adjusted to 200 mW·cm-2. The reactor was evacuated by a vacuum pump, and then the light source was turned on for continuous irradiation for 30 min to synthesize Cu 3 Ni 1 -SrTiO 3 . The synthesized composite material was washed three times with deionized water to remove residual ethanol and nitrate ions, and finally dried under vacuum for 5 h. Under ultrasonic conditions, 20 mg of the photocatalyst was mixed with 5 mL of deionized water and dispersed in a quartz groove with a diameter of 45 mm, and then placed in a vacuum oven at 60 °C and dried for 5 h to obtain a thin film catalyst.

[0049] Cu 3 Ni 1 -SrTiO 3 The photocatalytic CO 2 reduction performance evaluation was the same as that in Example 1. Figure 8 Shown is Cu 3 Ni 1 -SrTiO 3 Product performance graph of the catalyst under continuous light irradiation for 4 h, with the methane production of the main product reaching 1563.2 μmol g -1, The electron selectivity reaches 85.5%. It shows excellent photocatalytic activity without any sacrificial agent and cocatalyst, and has excellent commercial value. At the same time, Figure 9 is Cu 3 Ni 1 -SrTiO 3 The methane production of the catalyst almost linearly increases and shows no obvious attenuation within 4 consecutive cycles, indicating its good catalytic stability.

[0050] Example 4 Cu 5 In 1 -Cu 2 Preparation and Photocatalytic CO 2 Reduction Performance Evaluation

[0051] 500 mg of Cu 2 O was weighed and dispersed in 70 mL of absolute ethanol in Beaker 1, and ultrasonic treatment was carried out to ensure uniform dispersion. Then, copper nitrate ethanol solution and indium nitrate ethanol solution with a concentration of 1 mg / mL were prepared and ultrasonic-treated for 30 min to obtain a uniform solution. Subsequently, 24.1 mL of copper nitrate ethanol solution and 6.0 mL of nickel nitrate ethanol solution were respectively added to Beaker 1. The mixed solution was transferred to a glass reactor equipped with a magnetic stirrer and stirred. About 10 cm above the reactor, a xenon lamp source simulating sunlight was used for irradiation, and the light intensity was adjusted to 200 mW·cm-2. The reactor was evacuated by a vacuum pump, and then the light source was turned on for continuous irradiation for 30 min to synthesize Cu 5 In 1 -Cu 2 O. The synthesized composite material was washed three times with deionized water to remove residual ethanol and nitrate ions, and finally dried under vacuum for 5 h. Under ultrasonic conditions, 20 mg of the photocatalyst was mixed with 5 mL of deionized water and dispersed in a quartz groove with a diameter of 45 mm, and then placed in a vacuum oven at 60 °C for drying for 5 h to obtain a thin film catalyst.

[0052] Cu 5 In 1 -Cu 2 O Catalyst Photocatalytic CO 2 Reduction performance evaluation is the same as that in Example 1. Figure 10 As shown, for the Cu 5 In 1 -Cu 2 O catalyst, the product performance graph under continuous light irradiation for 4 h shows that the methane production of its main product reaches 1264.6 μmol g -1 , and the electron selectivity reaches 84.0%. It shows excellent photocatalytic activity without any sacrificial agent and cocatalyst, and has excellent commercial value.Figure 11 is Cu 5 In 1 -Cu 2 The methane production of the In-Cu-O catalyst almost linearly increases and shows no obvious decay within four consecutive cycle periods, indicating its good catalytic stability.

[0053] Example 5 Cu 3 Bi 1 -WO 3 Preparation of the Cu-Bi-WO catalyst and evaluation of its photocatalytic CO 2 reduction performance

[0054] 500 mg of WO 3 was weighed and dispersed in 70 mL of absolute ethanol in Beaker 1, and ultrasonic treatment was carried out to ensure uniform dispersion. Then, copper nitrate ethanol solution and bismuth nitrate ethanol solution with a concentration of 1 mg / mL were prepared and ultrasonically treated for 30 min to obtain a uniform solution. Subsequently, 21.8 mL of copper nitrate ethanol solution and 12.1 mL of bismuth nitrate ethanol solution were respectively added to Beaker 1. The mixed solution was transferred to a glass reactor equipped with a magnetic stirrer and stirred. About 10 cm directly above the reactor, a xenon lamp source simulating sunlight was used for irradiation, and the light intensity was adjusted to 200 mW·cm-2. The reactor was evacuated by a vacuum pump, and then the light source was turned on for continuous irradiation for 30 min to synthesize Cu 3 Bi 1 -WO 3 . The synthesized composite material was washed three times with deionized water to remove residual ethanol and nitrate ions, and finally dried under vacuum for 5 h. Under ultrasonic conditions, 20 mg of the photocatalyst was mixed with 5 mL of deionized water and dispersed in a quartz groove with a diameter of 45 mm, and then placed in a vacuum oven at 60 °C for drying for 5 h to obtain a thin film catalyst.

[0055] Cu 3 Bi 1 -WO 3 The evaluation of the photocatalytic CO 2 reduction performance of the Cu-Bi-WO catalyst is the same as that in Example 1. Figure 12 Shown is the product performance graph of the Cu-In-Cu-O catalyst under continuous light irradiation for 4 h, and the methane production of its main product reaches 517.2 μmol g 5 In 1 -Cu 2 O, and the electron selectivity reaches 85.1%. -1 , and the electron selectivity reaches 85.1%. Figure 13 is Cu 3 Bi 1 -WO 3The methane production of the catalyst increased almost linearly and without obvious attenuation within four consecutive cycles, indicating its good catalytic stability.

[0056] Control Example 1 Substrate material TiO 2 、SrTiO 3 、Cu 2 O、WO 3 Photocatalytic CO 2 Reduction performance evaluation of TiO 2 、SrTiO 3 、Cu 2 O、WO 3 Photocatalytic CO reduction performance evaluation of the catalyst is the same as that in Example 1. 2 The same as in Example 1. Figure 14 The product distribution diagram of the control catalyst under continuous light irradiation for 4 h is shown. As can be seen from the figure, the methane production of TiO 2 、SrTiO 3 、Cu 2 O、WO 3 is 88.25 μmol g -1 、28.56 μmol g -1 、10.33 μmol g -1 、4.32 μmol g -1 in turn. The electron selectivities of methane are 79.5%, 64.0%, 36.1%, and 47.8% in turn. These results show that, whether it is methane production or electron selectivity, the performance of the control catalyst is significantly lower than that of the composite catalyst loaded with alloy quantum dots, further proving the effectiveness and superiority of copper-based alloy quantum dot modification in improving photocatalytic performance.

[0057] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements can still be made, and these improvements should also be regarded as the protection scope of the present invention.

Claims

1. A type of copper-based alloy quantum dot / metal oxide composite catalyst, characterized in that: The catalyst is formed by depositing copper nitrate and metal nitrate in different molar ratios on a metal oxide substrate under light conditions, wherein the deposited alloy has a nanometer scale.

2. The copper-based alloy quantum dot / metal oxide composite catalyst according to claim 1, characterized in that: The deposited metal is a non-noble metal element; the average size of the alloy is 1-2 nm; and the loading mass percentage in the copper-based alloy quantum dot / metal oxide composite catalyst is 0.9-1.5%.

3. The copper-based alloy quantum dot / metal oxide composite catalyst according to claim 1, characterized in that: The element that forms an alloy with the copper element in copper nitrate includes one of Co, Ni, In, Bi, and Ln (Ln=La, Ce, Pr, Nd, Sm, Gd).

4. The copper-based alloy quantum dot / metal oxide composite catalyst according to claim 1, characterized in that: The expression of the composite catalyst is: Cu x Ln y -TiO2, Cu x Co y -TiO2, Cu x Ni y -SrTiO3,Cu x In y -Cu2O, Cu x Bi y -WO3 (1≤x, y≤7); wherein the ratio of x to y is optimized and determined by adjusting the molar ratio of nitrate.

5. The method for preparing a copper-based alloy quantum dot / metal oxide composite catalyst according to any one of claims 1 to 4, characterized in that: The catalyst is prepared by adding nitrates in different molar ratios to prepare a mixed solution and depositing the mixed solution on the surface of the metal oxide by an in-situ photodeposition method.

6. The method for preparing a copper-based alloy quantum dot / metal oxide composite catalyst according to claim 5, characterized in that: The preparation of the mixed solution and the deposition process include: 1) Ultrasonic dispersion of metal oxide (mass 100 mg to 500 mg) in anhydrous ethanol; 2) copper nitrate and other metal nitrates are mixed in different molar ratios, anhydrous ethanol is added and ultrasonic treatment is performed (the total molar amount of nitrate is 0.05 mmol to 0.5 mmol); 4) injecting the nitrate solution prepared in step 2 into the solution in step 1; 4) transferring the mixed solution into a glass reactor with a transparent quartz light window on the top of the reactor; 5) Seal the reactor, add a stirrer and stir, and connect the reactor to a condensed water circulation system; 6) Using a xenon lamp to simulate sunlight to irradiate the mixed solution for 30 to 60 minutes; 7) Separate and wash the product obtained in step 6 with deionized water, dry and grind to obtain a composite photocatalyst.

7. The method for preparing a copper-based alloy quantum dot / metal oxide composite catalyst according to claim 6, characterized in that: In the step (1), the mass of the metal oxide is 100 mg to 500 mg, and the volume of anhydrous ethanol is 50 to 100 mL; in the step (2), the total molar amount of the nitrate is 0.1 mmol to 0.5 mmol; in the step (5), the rotor stirring speed is 300 to 450 rpm, and the condensed water temperature is controlled at 15 to 25° C.; in the step (6), the xenon lamp light source is placed at a height of 10 to 20 cm above the mixed solution; the wavelength range of the xenon lamp light is 320 to 780 nm; and the light intensity is controlled at 100 to 500 mW cm -2 ; The irradiation time is 20 to 60 minutes; The specific steps of step (7) are as follows: centrifuge the product after photodeposition at a speed of 9000 rpm for 10 minutes, then add deionized water for washing three times, and finally dry in a vacuum drying oven at 60°C for 12 hours.

8. The copper-based alloy quantum dot / metal oxide composite catalyst according to any one of claims 1 to 4, characterized in that: The application of the catalyst is: used for photocatalytic CO2 reduction.

Citation Information

Cited By

  • Preparation method of super-crosslinked polymer supported copper-cobalt bimetallic composite catalyst

    CN120738683A